Addressing the urban poverty agenda in Bangladesh : critical issues and the 1995 survey findings - Islam, Nazrul; Asian Development Bank. (Dhaka : University Press, 1997)
Contributed articles.
"Published for the Asian Development Bank."
Includes bibliographical references (p. [305]-313) and index.
Keywords: Urban poor -- Bangladesh; Bangladesh -- Social policy